2019
DOI: 10.3329/cmoshmcj.v17i2.39775
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Prescribing Pattern at Outpatient Department of A Tertiary Medical College Hospital

Abstract: Background: In order to improve the prescription quality and promoting rational prescription pattern, there is an obligatory need to investigate the factors that affect doctors' prescription patterns. The study was conducted to observe the antibiotics prescribing pattern at outpatient department of a tertiary medical college hospital. Methods: This was a descriptive cross sectional study in a tertiary medical college hospital during the period of January 2018 to June 2018 which was conducted on 300 presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…27 A study conducted in Bangladesh, however, reported that cephalosporins were the most frequently prescribed groups of antibiotics followed by macrolids. 28 By specific antibiotics, amoxicillin (28.5%) followed by ciprofloxacin (12%) and metronidazole (11.1%) were the most frequently prescribed antibiotics in the current study. This finding was consistent with similar study conducted in Ghana, in which amoxicillin (22.5%) followed by ciprofloxacin (18.4%) being the most frequently prescribed antibiotics.…”
Section: Discussionmentioning
confidence: 63%
“…27 A study conducted in Bangladesh, however, reported that cephalosporins were the most frequently prescribed groups of antibiotics followed by macrolids. 28 By specific antibiotics, amoxicillin (28.5%) followed by ciprofloxacin (12%) and metronidazole (11.1%) were the most frequently prescribed antibiotics in the current study. This finding was consistent with similar study conducted in Ghana, in which amoxicillin (22.5%) followed by ciprofloxacin (18.4%) being the most frequently prescribed antibiotics.…”
Section: Discussionmentioning
confidence: 63%
“…Health sector (combined by 'OR') (b) Geographic location (combined by 'OR') (c) and/or its indiscriminate use [17]. Studies reveal two or more antimicrobials to be commonly prescribed at a time in Bangladesh [14,15,18,19,20,22,30,31], and more antimicrobials to be prescribed in hospital settings compared to community settings [21]. Prescribing antibiotics without laboratory tests was quite common in Bangladesh due to reported lack of testing facilities [18,19,22].…”
Section: Amr (Combined By 'Or') (A)mentioning
confidence: 99%
“…Studies reveal two or more antimicrobials to be commonly prescribed at a time in Bangladesh [14,15,18,19,20,22,30,31], and more antimicrobials to be prescribed in hospital settings compared to community settings [21]. Prescribing antibiotics without laboratory tests was quite common in Bangladesh due to reported lack of testing facilities [18,19,22]. However, sometimes the qualified prescribers (e.g., in-service trainee doctors of medical college hospital) felt confident enough to select an appropriate antimicrobial and prescribe correct dose and duration based on clinical diagnosis [23].…”
Section: Amr (Combined By 'Or') (A)mentioning
confidence: 99%
“…In 2018, cefuroxime is the 6 th most commonly prescribed antibiotics in the present study. Ata and Biswas [10] reported that cefuroxime was the most commonly prescribed antibiotics (22.5%) followed by azythromycin (11.6%) cefixime (11.5%) ciprofloxacin (10.9%) flucloxacillin (10.9%) and metronidazole (8.7%). Coenen et al [11] reported that there is an increase of second and third-generation use, mainly cefuroxime, cefpodoxime and cefixime.…”
Section: Discussionmentioning
confidence: 99%